Análisis de frecuencias alélicas y genotípicas de las variantes CYP2A6*12 y rs16969968 de CHRNA5 y su asociación con el hábito de fumar y el índice de masa corporal (IMC) en sujetos jóvenes del noreste de México - Borrego Soto, Gissela; Costilla Esquivel, Antonio; Padilla Rivas, Gerardo Raymundo; Cázares Samaniego, Paulina Janeth; Posadas Valay, Rodolfo; Velasco Castañón, José Gerardo; Mercado Longoria, Roberto; Ortiz López, Rocío; Rojas Martínez, Augusto (2015)
Several studies have reported that variants rs16969968 G>A of the CHRNA5 gene and CYP2A6*12 of the CYP2A6 gene are associated with smoking and smoking refusal, respectively. In addition, some studies report that a higher cigarette consumption is associated with low body mass index (BMI). Aim: To analyze the allele and genotypic frequencies of these variants and their impact on smoking and BMI. Material and Methods: A blood sample was obtained and a survey about smoking habits was answered by 319 university students aged 18 to 35 years (127 women, 171 smokers), living in Northeastern Mexico. Genetic variants were studied by polymerase chain reaction/ restriction fragment length polymorphism and their frequencies were associated with smoking and BMI. Results: No associations were found between the analyzed variants and smoking in the study groups. However, there was an association among non-smoking subjects between the A allele of rs16969968 and high a BMI (p < 0.01). Conclusions: This last variant may be involved in food-addiction disorders.